Ferromagnetism induced by C doped graphene-like ZnO films with different concentrations. (September 2019) - Wen, Jun-Qing; Tong, Xin; Lei, Yu-Tian; Tian, Peng-Hui; Wu, Hua; He, Wan-Lin; Zhang, Jian-Min
Abstract: The geometrical and magnetic properties of C atoms doped graphene-like ZnO (g-ZnO) monolayer supercell with the concentrations of 6.25%, 12.5% 18.75% and 25% has been calculated using the first-principles method. The calculated results indicate that C doped g-ZnO monolayer causes the structural distortion. G-ZnO monolayer with one O atom substituted by one C atom is ferromagnetic (FM) half-metal. When the doped concentration of C is 12.5% 18.75% and 25%, the models present strong FM metal properties. The hybridization between C atoms and neighboring host atoms results in the spin polarization between C(2p)-Zn(4d)-O(2p), which causes strong FM properties. Highlights: C atoms replacing one or more O atoms causes the structural distortion. Doped g-ZnO monolayer with one or more C atoms exhibits strong magnetism. The hybridization between C atoms and neighboring host atoms results in the spin polarization between C(2p)-Zn(4d)-O(2p).